Factors Affecting the Export Value of Indonesian Natural Rubber Commodities - Farid Arifin; Nurul Anwar; Diah Setyorini Gunawan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
Rubber and articles thereof commodities are one of Indonesia's leading exports, and natural rubber dominates among those commodities. However, in the last decade, the export performance of natural rubber commodities has not been optimal, especially in the last three years as seen from the declining export value. The purpose of the study was to determine the effect of production, international prices, and also the exchange rate on Indonesia's natural rubber exports, as well as to see which factors had a dominant influence. The analytical method used is multiple regression using secondary data for a period of 30 years (1991-2020), the export value of natural rubber commodities, production, international prices, and exchange rates. Result of this study, production, international prices, and exchange rates have a positive and significant impact on the export value of Indonesia's natural rubber commodities. The production, international prices, and exchange rates together have a significant effect on the export value of Indonesia's natural rubber commodities. The international price factor is the most dominating factor in influencing the export value of Indonesia's natural rubber commodities.